2003
DOI: 10.1108/00400910310495996
|View full text |Cite
|
Sign up to set email alerts
|

The controversial role of personality traits in entrepreneurial psychology

Abstract: The usefulness of personality traits in the explanation and prediction of entrepreneurship is critically evaluated, and both contemporary theory and existing empirical findings are reviewed, emphasizing the need for conceptual clarity and methodological reform. Detailed recommendations for future research are outlined, and this critique is complemented by a detailed case study of a practical research design drawn from an ongoing project. Taken together, these provide a powerful illustration of how abstract pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 7 publications
2
89
1
5
Order By: Relevance
“…These studies have confirmed that further research is needed to evaluate the role of personality in relation to entrepreneurship (Llewellyn & Wilson, 2003). Similarly, calls have recently arisen to make use of comprehensive and valid psychological frameworks to investigate the relationships between a business leader's personality attributes and firm performance (Hiller & Hambrick, 2005;Cannella & Monroe, 1997).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…These studies have confirmed that further research is needed to evaluate the role of personality in relation to entrepreneurship (Llewellyn & Wilson, 2003). Similarly, calls have recently arisen to make use of comprehensive and valid psychological frameworks to investigate the relationships between a business leader's personality attributes and firm performance (Hiller & Hambrick, 2005;Cannella & Monroe, 1997).…”
Section: Introductionmentioning
confidence: 68%
“…Previous efforts to investigate the relationship between personality traits and entrepreneurship have centred on the use of narrow traits such as risk-taking, locus of control and need for achievement (Llewellyn & Wilson, 2003). These studies have confirmed that further research is needed to evaluate the role of personality in relation to entrepreneurship (Llewellyn & Wilson, 2003).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The first group of researchers argues that education can improve an individual's creativity, flexibility, self-direction and ability to respond to widely variable situations and thus contribute to innovative behaviours (Llewellyn & Wilson, 2003;Rauch & Frese, 2000;Shook, Priem, & McGee, 2003). In particular, individuals with educational attainment know when, how and where to start a company (Ronstadt, 1985).…”
Section: Socio-cultural Background and Entrepreneurial Intentionmentioning
confidence: 99%
“…In fact, personality and personality traits have increasingly been examined and used as a means of employee selection as well as employee development (Barrick and Mount, 1991;Bergner et al, 2010). Personality is defined as qualities that an individual possesses and forms his or her character (Waite and Hawker, 2009) while personality traits are the constructs that are more specific and they explain why different people behave, act and react differently (Llewellyn and Wilson, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%